(untitled) (Journal of Parents and Teachers, 2018)
We propose a reflection about how to present the social approach in the scientific-technological curriculum from a mathematical perspective. We advocate for a mathematics and science as knowledge in construction, product of the historical necessities and in a determined context, promoting the study of the scientific-technological aspects in their sociocultural environment.